2019
DOI: 10.1002/lno.11345
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics supports the presence of G protein‐coupled receptor‐based signaling in unicellular marine eukaryotes

Abstract: Being abundant primary producers, single-celled eukaryotic diatoms and dinoflagellates dominate marine food webs and significantly impact the ecology of the oceans. These organisms face competition and predation which have contributed to the evolution of chemical defenses and their ability to sense chemical cues. Elucidating how these chemical cues are perceived by organisms requires identification of proteins involved in relaying chemical information to cells. The functions of G protein-coupled receptor (GPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Based on prior studies (Wohlrab et al 2010; Amato et al 2018; Li and Ismar 2018; Harðardóttir et al 2019; Mojib and Kubanek 2020), copepodamides were hypothesized to act as agonists of GPCRs, triggering a signaling cascade that results in amplified toxin production in A. minutum . However, when the GPCR inhibitor SCH‐202676 was applied to A. minutum to prevent binding of ligands to GPCRs (Fawzi et al 2001), toxin concentrations rose significantly (GPCR inhibition: F 1,32 = 9.3, p = 0.004; Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on prior studies (Wohlrab et al 2010; Amato et al 2018; Li and Ismar 2018; Harðardóttir et al 2019; Mojib and Kubanek 2020), copepodamides were hypothesized to act as agonists of GPCRs, triggering a signaling cascade that results in amplified toxin production in A. minutum . However, when the GPCR inhibitor SCH‐202676 was applied to A. minutum to prevent binding of ligands to GPCRs (Fawzi et al 2001), toxin concentrations rose significantly (GPCR inhibition: F 1,32 = 9.3, p = 0.004; Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the diatom Skeletonema marinoi , copepod cues boosted cAMP activity (Amato et al 2018) whereas in A. tamarense cAMP was reduced (Wohlrab et al 2010). This is likely due to major differences in the structures and functions of the predominant GPCRs and G protein signaling in diatoms and dinoflagellates (Mojib and Kubanek 2020). Perhaps copepodamides interact further upstream in the pathway in diatoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not clear what is their function in microbial eukaryotes, such as dinophytes [83]. However, recently, it was suggested that they are involved in G protein-coupled receptor-based signalling in Dinophyta [84].…”
Section: Discussionmentioning
confidence: 99%